The first wasps from the Upper Jurassic of Australia (Hymenoptera: Evanioidea, Praeaulacidae) STEFANIE K. - Oberprieler, Stefanie K.; Rasnitsyn, Alexandr P.; Brothers, Denis J. (Zootaxa, 2012)
The Hymenoptera fossils discovered in the Upper Jurassic Talbragar Fish Bed in Australia are described and illustrated. Gulgonga beattiei gen. et sp. nov., described from a single specimen, is assigned to the apocritan subfamily Praeaulacinae based primarily on wing venation, mesosomal structure, metasomal articulation, ovipositor shape and antennal form. It is the second member of Praeaulacidae known from Australia; all other praeaulacids have been found in the northern hemisphere. A second Talbragar wasp fossil is assigned to Apocrita incertae sedis because it is too poorly preserved for proper identification.